(untitled) (Research And Development Journal Of Education (RDJE), 2026)
This study aims to analyze the development of research on transformational leadership in education, focusing on its impact on teacher performance, job satisfaction, motivation, and professional development. The approach used was bibliometric and a systematic literature review of 24 Scopus indexed articles from 2018 to 2025. The results of the analysis show that the dominant theme in this literature focuses on the relationship between transformational leadership and improved teacher performance, which is accompanied by higher engagement and motivation. Some of the main thematic clusters that emerged include: (a) empowerment and cultural change in schools, (b) teachers’ professional development through continuous training, (c) teachers’ job well-being, and (d) indirect impacts on students’ academic outcomes. The methodology used was mostly quantitative (10 articles), followed by mixed methods (6 articles) and qualitative (5 articles). Research gaps were identified in the lack of multi-level and longitudinal studies exploring long-term effects. The novelty of this research lies in the synthesis of evidence on the impact of transformational leadership, with a focus on teacher motivation and well-being. This research provides in-depth insights into the implementation of transformational leadership and directs further research on the combination of leadership styles in multi-level and longitudinal contexts.